The Impact of Mining Activities on Ecology Condition and in the Marisa Watershed Pohuwato Regency, Gorontalo Province - Feri Novriyal; Herlindah; Nur Meyla Ulfiana Botutihe; Fajran Bentearu; Iswan Dunggio; Fitryane Lihawa; Marini Susanti Hamidun (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The Marisa watershed with an area of 248.43 km2 is one of the watersheds in the Paguyaman Watershed. The upstream area of the Marisa Taluduyunu River in Marisa District empties into the coastal waters of the south coast of Pohuwato Regency. Almost all the riverbanks are used by local communities for traditional gold mining. Some of these mining businesses are managed traditionally using mercury, and the waste produced without being managed is directly thrown into the environment. This research aims to analyze the impact of illegal mining on land and the Marisa watershed. The method used to analyze the data is descriptive qualitative based on field observation data and literature studies. Observations from various mining locations show that the removal of the topsoil causes the soil to be unproductive for plant growth around the mining location or site. River pollution is also one of the impacts that can be seen at mining locations. Gold ore processing, especially if the amalgamation process uses mercury, spreads mercury to environmental components, especially water quality and aquatic biota. The water quality that is most affected by mining and gold ore processing activities includes increased concentrations of suspended solids and mercury concentrations. The impact of traditional gold mining activities greatly affects the water quality components, namely, total suspended solids and dissolved mercury concentration. The concentration of total suspended solids poses a risk of harm to aquatic organisms. Concentrations of dissolved mercury metal have the potential to reduce the quality of fishery products.